Mediterranean landscapes in post antiquity : new frontiers and new perspectives - Gelichi, Sauro; Corrò, Elisa (Archaeopress archaeology., 2019)
Mediterranean Landscapes in Post Antiquity: New frontiers and new perspectives' highlights the fact that the study of landscape has in recent years been a field for considerable analytical archaeological experimentation. This new situation has made it possible to rethink the orientation of some theoretical approaches to the subject; equally these methods have been profitably used for the formation of a new theoretical and conceptual framework. These analytical trends have also featured in the Mediterranean area. Although the Mediterranean is the home of classicism (which also defines a particular archaeological methodology), it has seen the implementation of projects of this new kind, and in regions of Spain and Italy, after some delay, the proliferation of landscape archaeology studies. There are examples of more-or-less sophisticated postcolonial archaeological work, albeit conducted at the same time as examples of unreconstructed colonial archaeology. It is not easy to resolve a situation like this which requires the full integration of the different national archaeological cultures into a truly global forum. But some reflection on the cultural differences between the various landscape archaeologies, at least in the West is required. These considerations have given rise to the idea of this book which examines these themes in the framework of the Mediterranean area.